Knowledge, attitudes and practices regarding the Pap test among women in northeastern Brazil - Albuquerque, Carla Lorenna Ferreira de; Costa, Marla da Paschoa; Nunes, Felipe Moreira; Freitas, Roberto Wagner Junior Freire de; Fernandes, José Veríssimo; Rego, Juciane Vaz; Barreto, Humberto Medeiros (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: The Papanicolaou (Pap) test has been shown to be effective in preventing cervical cancer. However, both the national and international literature shows that Pap testing has not reached the level of coverage desired. The objective of this study was to assess women’s knowledge, attitudes and practices regarding the Pap test and to investigate whether there are any associations between these three factors and the women’s sociodemographic characteristics. DESIGN AND SETTING: Cross-sectional descriptive study conducted in Floriano, Piauí. METHODS: The study was conducted among 493 women between November 2009 and December 2010. A questionnaire with precoded questions was used, and the responses were analyzed in terms of appropriateness in relation to the Pap test. RESULTS: The degrees of adequacy of knowledge, attitudes and practices regarding the Pap test were 36.7%, 67.2% and 69.6%, respectively. Among the main barriers against testing, absence of symptoms and a sense of embarrassment were the most notable. CONCLUSIONS: Women who visit doctors periodically had the most appropriate practices regarding the Pap test, but their knowledge of the procedure was poor. This suggests that these women were not receiving adequate information about the benefits of periodic testing.